1998
DOI: 10.1002/aic.690440705
|View full text |Cite
|
Sign up to set email alerts
|

Growth regime map for liquid‐bound granules

Abstract: A regime map of granule growth behavior is proposed based on granule deformation during collision and the granule liquid content measured as the maximum pore saturation. The granule deformability on collision is represented by a deformation number, which is a ratio of granule impact energy to the plastic energy absorbed per unit strain. Granule growth regimes such as steady growth, induction, nucleation, crumb, and sluny are defined. This regime map qualitatively explains the uariatiom in granulation behauior.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
109
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 238 publications
(113 citation statements)
references
References 22 publications
3
109
0
1
Order By: Relevance
“…Former researchers described that the high shear granulation process could be divided into three phases, namely, nucleation, growth, and breakage (27,28). As shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Former researchers described that the high shear granulation process could be divided into three phases, namely, nucleation, growth, and breakage (27,28). As shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This can be explained, firstly, by the existence of a critical speed N c (see Section 3.2.1) for optimal granulation and growth regimes. In granulation processes, two main growth regimes have been identified [17]: steady growth and induction type behaviour. Steady growth occurs when the deformability is high.…”
Section: Comments and Discussionmentioning
confidence: 99%
“…Iveson et al [22,23] proposed a granule growth regime map, shown in Figure 1, in which the granule growth behavior is expressed as the granule pore saturation in comparison to granule deformation during impact. In general, the growth regime map is divided into two categories: the steady growth and induction growth.…”
Section: Granule Growth Regime Mapmentioning
confidence: 99%
“…The nucleation phase is fundamentally directed by wetting thermodynamics and kinetics, whereas granule-granule collisions during the steady growth phase are more dependent on the visco-elastic properties of the granules. In order to achieve a successful granule-granule coalescence in fluidized bed systems, the kinetic energy of the colliding granules must be dissipated in the viscous liquid layer on the granule surface [20][21][22][23]. The granule's liquid layer thickness, liquid ratio and mass strongly affect the Young's modulus of elasticity [24], which further influences the AE produced by particle impact [25].…”
Section: Granulation Rate Processesmentioning
confidence: 99%